2008
DOI: 10.1007/s00705-007-1104-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent Korean isolates of duck hepatitis virus reveal the presence of a new geno- and serotype when compared to duck hepatitis virus type 1 type strains

Abstract: The authors regret that a sequencing error was made in 3D region of DHV-HS in the above paper. The new sequence of DHV-HS has been updated in GenBank (DQ812094). In re-analysis of the Simplot, there is no clear signal of recombination between the two strains (DHV-HS and DHV-HSS) so that the SimPlot analysis (Fig. 2) and related paragraphs have become obsolete. The related paragraphs are as follows:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Based on phylogenetic analyses and neutralization tests, DHAVs are classified into three genotypes: DHAV-1, DHAV-2, and DHAV-3. There is no cross-neutralization between genotypes [5,6]. According to previous studies, DHAV-1 is widely distributed in China [7][8][9], DHAV-3 has been reported in Korea and China [5], whereas DHAV-2 has been detected only in Taiwan [6].…”
Section: Introductionmentioning
confidence: 89%
“…Based on phylogenetic analyses and neutralization tests, DHAVs are classified into three genotypes: DHAV-1, DHAV-2, and DHAV-3. There is no cross-neutralization between genotypes [5,6]. According to previous studies, DHAV-1 is widely distributed in China [7][8][9], DHAV-3 has been reported in Korea and China [5], whereas DHAV-2 has been detected only in Taiwan [6].…”
Section: Introductionmentioning
confidence: 89%
“…Discussion DVH, especially the new type of DVH caused by DHAV-C and reported in recent years in mainland China and Korea (Kim et al, 2007;Wang et al, 2008), is a severe disease resulting in huge economic losses. This disease has brought great difficulties in the prevention and control of the disease in duck-rearing regions.…”
Section: Methodsmentioning
confidence: 99%
“…They are widely epidemic in duckrearing areas worldwide. The pathogen of a new-type of DVH prevalent in Asia in recent years was proved to be a picornavirus (Kim et al, 2007;Tseng et al, 2007;Wang et al, 2008). The serotype of this new type of DHV was not related to conventional DHV-1, although they both belong to the Picornaviridae family (Kim et al, 2007;Tseng et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations